Puppets theater importance in contemporary society: حسين خميس علوان الأنصاري (Al-Academy, 2020)
Puppets theaters importance in contemporary society Throughout history puppets theater recognized to achieve constant successes, despite other expressive arts competitors, through diversity of forms topics and ways of direction whether for adults or children’s audients. Today every society has its own puppets, of which the forms are inspired by the cultural heritage. to express its cultural identity. Each of those puppets is c by its powerful expression, going beyond the performance of human actors. Thanks to technology, puppets industry, production and direction has evolved in this study, we will identify puppets theatre, its types importance in modern society, and secret of its powerful expression to attract the audience.